Long-term outcomes after definitive radiotherapy with modern techniques for unresectable soft tissue sarcoma. (August 2022) - Allignet, Benoît; Waissi, Waisse; Geets, Xavier; Dufresne, Armelle; Brahmi, Mehdi; Ray-Coquard, Isabelle; Blay, Jean-Yves; Bouhamama, Amine; Meeus, Pierre; Vaz, Gualter; Gouin, Francois; Moncharmont, Coralie; et al.
Graphical abstract: Highlights: Definitive radiotherapy in unresectable soft tissue sarcoma is controversial. Available data are scarce, especially for intensity-modulated radiotherapy. One of five patients presented partial response. Cumulative incidence of local failures was <50% at five years. A third of patients were alive at three years. Abstract: Introduction: The use of definitive radiotherapy (dRT) in unresectable soft-tissue sarcomas (STS) is still controversial and recent data are scarce. We report clinical results of this therapeutic option. Methods: We retrospectively included STS patients treated between 2009 and 2020, with dRT for unresectable or with a measurable residual disease after R2 surgery. Response rate, local failure (LF), progression-free survival (PFS) and overall survival (OS) were evaluated. Results: 116 patients with localized/locally advanced STS were treated from 2009 to 2020, with a median age of 71 years (range 18–92). Most tumors were deep-seated (96.6%), grade 2–3 (85.1%), located in the trunk or extremities (74.2%). Helical tomotherapy, volumetric modulated arc therapy, or stereotactic radiotherapy was performed in 39.7%, 19% and 8.6% of patients, respectively. The median equivalent dose in 2 Gy fractions (EQD2) was 60 Gy (IQR 52–65). At first follow-up, 66 (58.9%) and 25 (22%) patients had stable disease and partial response. After a median follow-up of 54.8 months (IQR 40.3–95.4), 3-year LF, PFS and OS were 43.2%, 16.6% and 34%, respectively. Median OS was 21.4 months (95%CI 14–26). The multivariate analysis identified grade 3 and AJCC T3-T4 stage to be associated with both shorter PFS and OS (all p < 0.001). Macroscopically incomplete resection and EQD2 ≥ 64 Gy were associated with better OS ( p = 0.016 and p = 0.007). Acute and late severe adverse events occurred in 24 (19.7%) and 5 (4.3%) patients. Conclusion: In unresectable STS patients, definitive modern radiotherapy is a safe and effective treatment yielding long term control in selected patients.